HUBUNGAN KETUBAN PECAH DINI DAN USIA KEHAMILAN IBU DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RSUD KABUPATEN INDRAMAYU TAHUN 2022: THE RELATIONSHIP BETWEEN AMNIOTIC EARLYCAH AND MATERNAL GESTATIONAL AGE WITH THE INCIDENCE OF NEONATORAL ASPHYXIA IN RSUD KABUPATEN INDRAMAYU - Hikmawati, Kitri; Purbasary, Eleni Kenanga; Riyanto; Parawangsa, Khofifah Indar (WELL BEING, 2023)
Early rupture of the amniotic is one of the causes of asphyxia because the rupture of the oligohydramnios membrane that presses on the umbilical cord so that it experiences asphyxia so that gestational age is related to asphyxia because the aging process causes the placenta to function less optimally so that it can cause asphyxia. This purpose is to determine the relationship between early rupture of amniotics and maternal gestational age with the incidence of neonatoral asphyxia at the RSUD Kabupaten Indramayu in 2022. This studied used a cross-sectional design analytical descriptive method using a Retrospective approach, the population in my studied was all babies who experienced asphyxia with a total sample of 80 respondents using simple random sampling while the research instrument used a checklist sheet of research data using secondary data from medical records, and data analysis techniques using the Chi Square test by reading using pearson chi square. The results of this studied showed no relationship between the amniotic rupture early and the incidence of neonatoral asphyxia (p-value 0.408), and there was no relationship between the gestational age of the mother and the incidence of neonatoral asphyxia (p-value 0.424), because the results of this studied did not have a relationship, it was believed that there were other factors that influenced the incidence of neonatoral asphyxia, namely factors of maternal state, preeclampsia, bleeding, and old or stalled partus. The advice in this studied is that it is hoped that future studies will examine samples of babies who have asphyxia and do not experience asphyxia because it is to be a comparison and further analysis is carried out to make it more valid.